PP74 Taking A Lifecycle Approach To Scottish Medicines Consortium Budget Impact Analysis. (23rd December 2022) - Booth, Corinne; Dimitrova, Maria; Henriquez, Alex; Hislop, Jennifer; Manson, Jan; Wright, Helen
Abstract : Introduction: The Scottish Medicines Consortium (SMC) conducts early health technology assessment of new medicines in Scotland. While budget impact is not a factor in decisions on reimbursement, budget impact information is provided initially through horizon scanning reports for high impact medicines (estimated net budget impact >GBP 500, 000 [EUR 585, 710] per annum) to aid financial planning and implementation of advice at the local level, and later through budget impact templates from the submitting company issued alongside SMC advice. This research aimed to understand how the information is used and to evaluate the benefits of a lifecycle approach to budget impact analysis. Methods: Health Board users of the budget impact templates were surveyed to explore the degree of utilization and identify areas for improvement, including the need to cross-validate the horizon scanning estimates with those of the submitting company. Responses were analyzed quantitatively and qualitatively, with comments coded in Nvivo (QSR International) and themes established through thematic analysis. Results: The initial responses received (n=17) provided representation from 57 percent of Health Boards (i.e., payers) covering 79 percent of the population. Preliminary results showed that while the budget impact templates were valued, 69 percent of respondents found them 'somewhat useful', suggesting scope for improvement. Almost half (48%) of the respondents used the templates for high impact medicines, with only 30 percent using them for all medicines. The majority (76%) of those surveyed thought there would be value in linking budget impact information throughout the SMC process. An emerging theme was that some users found the templates complex and inflexible, and that a simpler, more adaptable tool to aid the planning process would be welcomed. Priorities identified for improving template included adapting them to the local population and adjusting medicine prices to reflect confidential discounts. Conclusions: This research suggests that budget impact information is valued by Health Boards and that there is strong support for linking budget impact estimates and engaging stakeholders throughout a medicine's lifecycle. Simplifying the templates, increasing their adaptability, and providing guidance and training in their use will be key steps in improving this important part of SMC process.